THE USE OF ILLUSTRATIONS IN THE STUDENTS' READING COMPREHENSION : A Quasi Experimental Study in a private College in Bandung - Purwanti, - (2019)
This study investigated the effectiveness of illustrations on the students' reading comprehension and the students' attitude toward the use of illustrations in their reading comprehension. The aim is to determine whether or not illustrations affect the students' reading comprehension and their attitude. This study involved one experimental group and one control group as participants. The participants were asked to do pre-test and post-test. Once the participants had experienced both tests, they filled out the questionnaires and answered the interview. The participants' test showed different score between the control and the experimental group. In the control group, the scores of pre-test and post-test were similar, there was no significant difference after post-test, in other words, the improvement between pre-test and post-test was low. In the experimental group, the scores of pre-test and post-test were not similar, there was a significant difference after post-test, in other words, the improvement between pre-test and post-test was higher than the improvement in the control group. The questionnaire result showed most of the students agreed on the effectiveness of illustrations in helping their reading comprehension. The interview result revealed most of the students had positive response toward the use of illustrations in helping their reading comprehension. The use of illustrations, to some degree, is effective to improve the students' reading comprehension as well as the students' motivation.